Minimizing bias when using artificial intelligence in critical care medicine - Ranard, Benjamin L.; Park, Soojin; Jia, Yugang; Zhang, Yiye; Alwan, Fatima; Celi, Leo Anthony; Lusczek, Elizabeth R. (Journal of critical care, 2024)
•As artificial intelligence (AI) use in critical care increases, identifying and minimizing sources of bias is essential•Bias can be introduced (and be minimized) at all stages of the AI lifecycle•Reliance on AI in clinical practice without addressing bias may result in unfair and inequitable treatment of patients•Diverse, multidisciplinary teams that are attuned to sources of bias may have the best chance of minimizing bias in AI